(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The oil composition of Cassia alata seed collected from three different districts of Bangladesh was investigated. All the seed samples contain about 3.2 % oil. The triglyceride component of the oil varied from 91.5 to 92.0 % diglyceride from 3.4 to 3.9 % and monoglyceride from 1.5 to 2.1 %. The lipid components were almost the same in all the samples, the neutral lipid accounted for over 93 % of the total lipids present. The analysis of the fatty acid composition showed 25.6 % oleic acid, 45.5 % linoleic acid, 18.7 % palmitic acid, 3.5 % stearic acid, 3.4 % arachidic acid and 3.2 % behenic acid. Bangladesh J. Sci. Ind. Res. 41(1-2), 83-88, 2006